Acute cytomegalovirus infection complicated by venous thrombosis: a case report - Parola Philippe; Granel Brigitte; Rovery Clarisse; Foucault Cédric; Brouqui Philippe (BMC, 2005)
Abstract Background CMV-induced vasculopathy and thrombosis have been reported, but they are rare conditions usually encountered in immunocompromised patients. However more and more complications of CMV infections are recognized in immunocompetent patients. Case presentation We present a case report of a previously healthy adult with cytomegalovirus infection that was complicated by tibiopopliteal deep venous thrombosis and in whom Factor V Leiden heterozygous mutation was found. Conclusion This new case report emphasizes the involvement of cytomegalovirus in induction of vascular thrombosis in patients with predisposing risk factors for thrombosis. It is necessary to screen for CMV infection in patients with spontaneous thrombosis and an history of fever.